PREVALENCE AND FACTORS ASSOCIATED WITH DIABETES-RELATED EMOTIONAL DISTRESS (DRED) AMONG FILIPINO ADULT PATIENTS WITH TYPE 2 DIABETES MELLITUS USING A VALIDATED FILIPINO VERSION OF THE DIABETES DISTRESS SCALE (DDS) - Mirano, Carissa Rae; Dampil, Oliver Allan; Tan, Hanna Clementine; Placino , Sienna (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Diabetes-related Distress refers to the significant negative psychological reactions related to having diabetes mellitus. There are limited studies involving diabetes distress and its association with glycemic control and other clinicodemographic factors among Filipinos. In addition, there is currently no Filipino-adapted Diabetes Distress Scale. This study aimed to translate the Diabetes Distress Scale into Filipino, and validate this version among Filipino Adult Patients with Type 2 DM, and assess the prevalence of diabetes-related distress and its association with Glycemic Control and other related factors. METHODOLOGY The English DDS was translated into the Filipino language and a subsequent cross-sectional validation study was done with 186 individuals with type 2 diabetes in a singlecenter tertiary hospital and assessed the prevalence and related factors of DRED. Descriptive statistics was used for categorical variables. Shapiro-Wilk test was used to determine the normality distribution. Continuous quantitative data were summarized using mean and standard deviation (SD), median, and interquartile range. Logistic regression was used to determine the association of clinicodemographic and metabolic factors with moderate to high diabetes-related distress. Odds ratios and corresponding 95% confidence intervals were reported. RESULTS The overall prevalence of diabetes distress for this study is 34.41% with a mean overall score of 2.02. The prevalence of moderate distress was highest for Regimen-related distress at 45.16% (95% CI: 37.87-52.61%), followed by Emotionalrelated distress at 39.78% (95% CI: 32.70-47.20%), and the lowest prevalence was found in the Physician-related distress domain at 11.29% (95% CI: 7.13-16.74%). Age was a significant predictor of diabetes distress (OR 0.97(0.95- 1), p = 0.04). In contrast, educational level, marital status, socioeconomic status, duration of diabetes, presence of diabetic complications, number of medications, level of BMI, or glycemic control were not associated with diabetes distress. CONCLUSION This study has indicated that the Filipino DDS is a valid instrument in the assessment of diabetes-related distress among Filipino diabetic patients. A younger age was associated with the development of diabetes distress, while it was not associated with glycemic control and other related factors.